Investigating the Portuguese-English Bilingual Mental Lexicon: Crosslinguistic Orthographic and Phonological Overlap in Cognates and False Friends - Alves-Soares, Leonardo (Université d'Ottawa / University of Ottawa, 2020)
This dissertation investigates how cognates are organized in the bilingual mental lexicon and examines whether orthography in one language, via phonological representations, influences the processing of cognates and false friends in the other language. In light of the framework of two well-known models of bilingual visual word recognition, the Bilingual Interactive Activation (BIA) and the Bilingual Interactive Activation Plus (BIA+), the premise is that there is activation from orthography to phonology across a bilingual’s two languages and that this activation is modulated by the degree of orthographic and phonological code overlap. Two objective metrics were used to assess crosslinguistic similarity of Portuguese-English cognates and false friends that were selected for a cross-language lexical decision task with masked priming. Dynamic time warping (DTW), an algorithm that was originally conceived to compare different speech patterns in automatic speech recognition and to measure acoustic similarity between two time-dependent sequences, was used to compute crosslinguistic phonological similarity. The Normalized Levenshtein Distance (NLD), an algorithm that calculates the minimum number of single-character insertions, deletions or substitutions required to change one word into another and normalizes the result by their lengths, was used to compute crosslinguistic orthographic similarity. Portuguese-English bilinguals who acquired their second language after reaching puberty, and English functional monolinguals who grew up speaking primarily English were recruited to participate in the experimental task. Based on collected reaction time and accuracy data, mixed-effects models analyses are used to estimate the individual effects of crosslinguistic orthographic, phonological and semantic similarity and the role each of them, along with English proficiency, word frequency and length play in the organization of the Portuguese-English bilingual mental lexicon.
Keywords: bilingual mental lexicon; Portuguese; English; Portuguese-English bilinguals; English functional monolinguals; cognates; false friends; crosslinguistic overlap; crosslinguistic similarity; semantic; lexical decision task; LDT; masked priming; spreading activation; RHM; BIA; BIA+; Multilink; orthographic representations; phonological representations; dynamic time warping; DTW; Normalized Levenshtein Distance; NLD; mixed-effects models; lmer; glmer; reaction time; accuracy